WCDMA Systems Investigation with a Combination of Rake Receiver and Sub-Block Antenna Array Processing for Multiuser Detection - A.M. Al-Ja'afari, Mohannad; M.H. Al-Rikabi, Hussein; S.H. Al-Musawi, Raed; Mohammed A. M. Alrufaye, Mohammed; ., . (International Journal of Engineering and Technology, 2018)
This paper presents a new amalgamation of the RAKE receiver with three-fingers, and the Sub-Block-Based Normalized Least Mean Square-Despread-Respread Multi-Target Array (NLMS-DRMTA) algorithm for multiuser detection in Wideband Code Division Multiple Access (WCDMA) systems. The new method uses together temporal diversity and the space diversity, for getting a significant enhancement in Bit Error Rate (BER) performance, As well as reducing unwanted signals and Indirect signals effects. The combination of the rake receiver and the Sub-Block-Based algorithm was compared versus the single antenna CDMA and sample-based NLMS-DRMTA algorithm. This method can equip users more than the number of antenna array elements. Consequently, it is an extra productive strategy for expanding channel limit. Thus, it opens the route to an answer for limiting the impacts of multipath effects and interference from other users, in this manner enhancing the quality of services. Simulation results show that the sub-block algorithm overcomes the others without a rake system in both environments (AWGN or/and multipath fading). But with the rake, this algorithm will suffer from degradation in its BER performance. Also, the sample base algorithm takes advantages performance in the presence of rake receiver.Â